Familial exudative vitreoretinopathy associated with familial thrombocytopathy. Issue 11 (November 1983) - Chaudhuri, P R; Rosenthal, A R; Goulstine, D B; Rowlands, D; Mitchell, V E
Abstract : Two families with familial exudative vitreoretinopathy were studied in which platelet aggregation defects were found in all the affected members. The major defect observed was absent platelet aggregation with arachidonic acid. In addition platelet aggregation with collagen and adrenaline was reduced in one severely affected member. The implication of the platelet aggregation defect in the pathogenesis of this retinal vascular disorder is discussed.